2016
DOI: 10.5539/ies.v9n7p1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Student Coregulation in Task Interpretation during Electronics Laboratory Activities

Abstract: Coregulation (CRL) is a transitional process in which students share problem-solving techniques and utilize self-regulated learning (SRL) when interacting with peers. Coregulation may help students to define and modify inconsistencies in their SRL strategy. Task interpretation is described as the critical first step in the SRL process, and it is a key determinant in setting the goals and strategies to accomplish those goals. Limited information exists regarding coregulation and task interpretation in the conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…While these measures of task awareness were not tied directly to comprehension measures, Schellings et al (1996) found performance on the selection task was positively related to final course grades. Other work has looked at the related constructs, task understanding and task interpretation (e.g., Hadwin et al, 2009 ; Lawanto et al, 2013 ; Rivera-Reyes et al, 2016 ). Much of this work has used task questionnaires that probed implicit, explicit, and socio-cultural aspects of task models in the context of a class project (e.g., a complex academic activity extended over time).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these measures of task awareness were not tied directly to comprehension measures, Schellings et al (1996) found performance on the selection task was positively related to final course grades. Other work has looked at the related constructs, task understanding and task interpretation (e.g., Hadwin et al, 2009 ; Lawanto et al, 2013 ; Rivera-Reyes et al, 2016 ). Much of this work has used task questionnaires that probed implicit, explicit, and socio-cultural aspects of task models in the context of a class project (e.g., a complex academic activity extended over time).…”
Section: Discussionmentioning
confidence: 99%
“…However, the implicit questions also probe other aspects of task understanding such as resources needed and relevant course concepts important to task completion. These studies have found that task understanding, and in particular the implicit aspects, predicted both task and course performance (e.g., Miller, 2009 ; Oshige, 2009 ; Rivera-Reyes et al, 2016 ) and a post-task measure of conceptual understanding ( Rivera-Reyes et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have suggested that group learning offers a basis for social comparison and social learning (Solomon, Croft, & Lawson, 2010), and that teamwork quality and team diversity impact the effectiveness and quality of task completion (Curşeu, Schruijer, & Boroş, 2007;Menekse, Higashi, Schunn, & Baehr, 2017;Stevenson & Starkweather, 2010). For example, one study reported that students' approaches to understanding and solving a design task are influenced by their peers (Rivera-Reyes, Lawanto, & Pate, 2016). Passow & Passow's (2017) systematic literature review concluded that academia considered teamwork as one of the most important competencies that any engineering undergraduate students should have.…”
Section: Project Management In Engineering Designmentioning
confidence: 99%
“…Lubis and Nasution (2017) argue that each learner's initial task interpretation is unique because they have different levels of conceptual understanding. Fortunately, students' understanding has been shown to evolve as they work through the problem (Rivera-Reyes, 2015; Rivera-Reyes, Lawanto, & Pate, 2017) and interact with their peers (Rivera-Reyes, Lawanto, & Pate, 2016). As their task interpretation mature, students also adjust their approach to solving the problem (Abdillah, Nusantara, Subanj, Susanto, & Abadyo, 2016;Kahneman, 2003).…”
Section: Brief Relevant Literature Reviewmentioning
confidence: 99%